Media framing on the HIV/AIDS related epidemic / Mohd Shahnawi Muhmad Pirus, Ilias Md. Salleh and Mokhtar Muhammad. - Muhmad Pirus, Mohd Shahnawi; Md. Salleh, Ilias; Muhammad, Mokhtar (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2017)
Media plays an important role in the social landscape that helps to shape audience perceptions and it also facilitates public discourse and debate by defining acceptable parameters for discussion. According to Collins (2004), media serves as sense-makers to world and become the primary presenters of ideology for the large audience consumption, integrating the fact that media is vital as most commonly shared source of information. Controversial social issues and concerns become the common strengths for the conventional and mainstream media practices and it is represented in various media context (Hart, 1999). Based on Hart’s view, Piontek (1992) also claimed the issues on sexuality especially on homosexuality is dominantly geared by the media representation. He added these representations are fundamentally equipped with the intention to strengthen the society’s knowledge and perception towards their understanding on epidemic diseases such as the Acquired Immune Deficiency Syndrome (AIDS).